SOSIALISASI USAHA MINUMAN MADU LEMON SIAP MINUM MEREK HONEY LEMON SILINA HASIL PROSES PASTEURISASI DI KALANGAN GENERASI Z KOTA SURAKARTA MELALUI PREFERENSI KONSUMEN DAN HARGA PEMBELIAN - Lobes Herdiman; Susy Susmartini; Taufiq Rochman; R. Hari Setyanto; Ilham Priadythama (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
Honey and lemon are products of a wealth of natural resources in Indonesia. A new venture in the ready-to-drink honey lemon drink is Honey Lemon Silina, a pasteurized product produced by the Laboratory of Product Planning and Design at the Industrial Engineering Department Universitas Sebelas Maret, Surakarta. The importance of Honey Lemon Silina products has a business development focused on Generation Z (Gen. Z). This paper aims how to identify the results of socialization through focus group discussions on several questions from the questionnaire to Gen. Z in Surakarta City on aspects of consumer preference and the purchase price of Honey Lemon Silina brand honey drink products, including price, taste, product design, brand influence, and accessibility of sales locations. This paper focuses on the product features of Honey Lemon Silina, which can influence buying behavior among Gen. Z, including consumer preferences and differences in purchasing power. The result identifying factors influencing buying behavior among Gen. Z enables Honey Lemon Silina products to meet consumer expectations, needs, and demands.